Pembuatan Bahan Bakar Alternatif Dari Sampah Sayuran Hasil Pertanian Menggunakan Alat Distilator di Desa Sampajaya, Kecamatan Berastagi, Kabupaten Karo: Indonesia - Sidabutar, Rivaldi; Trisakti, Bambang; Irvan, Irvan; Al Fath, Muhammad Thoriq; Ginting, Muhammad Hendra Sahputra; Hanum, Farida; Taslim, Taslim; Sitepu, Rafael Aginta; Alamsyah, Vandria; Rasyid, Nashfin Nazli; Sinabang, Juwita Lestari (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Unsold vegetable waste from agricultural produce often rots and ends up being discarded at landfills, increasing waste volume and potentially causing environmental problems. To address this issue, vegetable waste can be processed into useful and marketable products such as bioethanol. Bioethanol is a renewable energy source obtained through the fermentation of biomass, including vegetable waste such as potatoes, tomatoes, carrots, mustard greens, and cabbage. In this community service program, an e-Bio production unit with a processing capacity of 5 liters has been designed, utilizing vegetable waste as raw material. The unit consists of pre-treatment equipment, a fermenter, and a distillation unit. The pre-treatment equipment includes an initial cooking tank, a crusher, and a pressurized tank. The fermenter tank is equipped with two manual paddle-type agitators with a diameter of 30 cm. Meanwhile, the distillation tank is made of stainless steel and equipped with a heater to heat the fermented solution and a cooling water tank to cool the evaporated e-Bio. The unit achieves a distillation efficiency of 95% with a production rate of 0.475 L/hour, producing 0.95 liters of ethanol after two hours of operation. The goal of this program is to implement the e-Bio production unit by utilizing vegetable waste as raw material, increase community or farmer income through e-Bio sales, and reduce the environmental impact caused by vegetable waste disposal.